(untitled) (Human Geographies – Journal of Studies and Research in Human Geography, 2025)
Human capital reflects the knowledge, competencies, and health people invest in and accumulate throughout their lives. Therefore, investing in people’s health, education, and skills is essential to developing human capital. The evaluation of human capital is very important for understanding the premises for future development at a territorial level and the impact that different development trajectories may have on economic performance and population wellbeing. Thus, identifying those areas with lower human capital is crucial for future economic and social prospects allowing authorities to elaborate targeted strategies to protect and invest in people in these areas. This paper aims to evaluate human capital at the national level, focusing on three main components: education, health and workforce. The research methodology is based on statistical analysis using available data on education, employment and health and spatial analysis using GIS. This study’s findings show that areas with higher human capital overlap with the most important Romanian cities and their surroundings (Bucharest, Timisoara, Cluj-Napoca, Iași, etc.), while lower human capital indices characterise extended rural areas located in the eastern part of the country and central, south and south-east, thus having different development premises. The present study contributes to a better evaluation and representation of human capital at the spatial level, pointing out the vulnerable areas from the point of view of education, workforce and health. Measures for uniformising and improving human capital will ensure the communities’ sustained economic and social development.